2011
DOI: 10.1182/blood-2010-10-312736
|View full text |Cite
|
Sign up to set email alerts
|

KDM2b/JHDM1b, an H3K36me2-specific demethylase, is required for initiation and maintenance of acute myeloid leukemia

Abstract: The histone H3 lysine 36 dimethylspecific demethylase KDM2b/JHDM1b, which is highly expressed in various human leukemias, was previously found to be important in regulating cell proliferation and cellular senescence. However, its functions in leukemia development and maintenance are unclear. Here, we demonstrate that ectopic expression of IntroductionPrevious studies have shown that human leukemic cells from the same patient are composed of heterogeneous cell populations with various proliferation capacities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 30 publications
6
147
1
2
Order By: Relevance
“…12 Furthermore, another study demonstrated that the demethylase enzymatic activity was required for leukemic transformation in a Hoxa9-Meis1-induced mouse BM transplantation model. 13 These findings suggest that Fbxl10 contributes to the development of tumor in vivo. The online version of this article contains a data supplement.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…12 Furthermore, another study demonstrated that the demethylase enzymatic activity was required for leukemic transformation in a Hoxa9-Meis1-induced mouse BM transplantation model. 13 These findings suggest that Fbxl10 contributes to the development of tumor in vivo. The online version of this article contains a data supplement.…”
mentioning
confidence: 89%
“…Previous studies have reported that Fbxl10 suppresses senescenceassociated cyclin-dependent kinase inhibitors (CDKIs) such as p15ink4b, p16ink4a, p18ink4c, and p57kip2 in murine blood cells. 12,13 Therefore, we investigated the possibility that suppression of these CDKI genes might account for the survival/proliferation advantage in Tg HSCs, which is reminiscent of the canonical class I mutations. The former 2 genes, p15ink4b and p16ink4a, were very weakly expressed in primary control HSCs, as reported in a previous transcriptome analysis 22 ; no expressional change of these genes was observed in Tg HSCs.…”
Section: Transgenic Expression Of Fbxl10 Induces Proliferation Advantmentioning
confidence: 99%
“…For instance, members of the JMJD2/KDM4 family, which can demethylate H3K9me3/me2 and H3K36me3/me2, have been found overexpressed in squamous cell carcinoma, breast cancer, and medulloblastoma 47--49 . Moreover members of the JARID1/KDM5 family that demethylate H3K4me3/me2 are overexpressed in breast and bladder cancers 50,51 , and FBXL10/KDM2B, specific for H3K36me3/me2, is overexpressed in leukaemia 52 . Somatic mutations and deletions have also been identified in the JmjC--domain containing demethylases, including the H3K27me3/me2 demethylase UTX/KDM6A that is found mutated in for instance multiple myeloma and renal cell carcinoma 27,28 , and in JARID1C/KDM5C and PHF8 in X--linked mental retardation patients 53,54 .…”
Section: The Jmjc--domain Familymentioning
confidence: 99%
“…Oligonucleotide sequences are listed in Table S1, including the Ink4 family primers. 47 PCR thermocycler conditions are available upon request.…”
Section: Pcr Quantitative-pcr (Qpcr) and Plasmid Constructionsmentioning
confidence: 99%